Mosaic metabolic ageing: Basal and standard metabolic rates age in opposite directions and independent of environmental quality, sex and life span in a passerine. (25th March 2021) - Briga, Michael; Verhulst, Simon
Abstract: Crucial to our understanding of the ageing process is identifying how traits change with age, which variables alter their ageing process and how these traits associate with fitness. Here we investigated metabolic ageing in outdoor‐living captive zebra finches experiencing foraging costs. We longitudinally monitored 407 individuals over 6 years and collected 3, 213 measurements of two independent mass‐adjusted metabolic traits: basal metabolic rate (BMRm ) at thermoneutral temperatures and standard metabolic rate (SMRm ), measured as BMRm but at ambient temperatures below thermoneutrality. We define mosaic or asynchronous ageing as the difference in standardized absolute ageing rates between traits, and we estimate the degree of asynchrony using the within‐individual correlation of change in trait values with age. BMRm decreased linearly with age, consistent with earlier reports. In contrast, SMRm increased linearly with age. The absolute standardized change with age was significantly faster for BMRm compared to SMRm, and the within‐individual correlation of age related change was negligible. To the best of our knowledge, this is the first quantification of SMRm ageing, and the finding that SMRm and BMRm age in opposite directions. Neither metabolic rate nor metabolic ageing rate were associated with variation in life span between individuals. Moreover, experimental manipulations of environmental quality that decreased BMRm and SMRm and shortened life span by 6 months (12%) did not affect the ageing of either metabolic trait. Females lived 2 months (4%) shorter than males, but none of the metabolic traits showed sex‐specific differences at any age. Our findings indicate, in contrast to the current view, that baseline energy requirements increase with age, because animals do not generally live in thermoneutral conditions, and illustrate the importance of studying the ageing phenotype in an ecologically realistic setting. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article.